The Effect of Organizational Culture on Employee Innovative Behavior - Bawab, Sarah (2022)
Innovation is important in any business organization because it allows companies to add value to their customers while simultaneously increasing profitability. Furthermore, organizations can establish significant competitive advantages over their competitors by implementing effective creative tactics, as innovation increases creativity, nature, and production. This study investigates the effect of different types of organizational culture on employee innovative behavior. It tests each of Cooperative Organizational Culture (COC), Innovative Organizational Culture (IOC), Hierarchical Organizational Culture (HOC), and Effective Organizational Culture (EOC) on Employee Innovative Behavior (EIB). It also examines the moderating role of transformational leadership on these relationships. The data was collected through 163 survey distributed among employees in Lebanon and the GCC region. The data was analyzed with SPSS software to check validity of suggested hypotheses. The study showed that Organizational culture positively affects employee innovative behavior and Transformational leadership moderates these relationships.